Edukasi Kesehatan Untuk Mengatasi Defisit Pengetahuan Pada Pasien Gout Arthritis - Sabil, Fitri A; Wijayaningsih, Kartika Sari; Fajriansi, Andi; Arna, Eva (PT.Mantaya Idea Batara, 2023)
Gout arthritis is a rheumatic disease that ranks third after rheumatoid arthritis. Gout arthritis is caused when the body has high levels of uric acid due to increased breakdown of purines. Purines are found in many foods and drinks. Therefore. It is important to provide education to the elderly regarding food and drink that is good for consumption so that inflammation and severe pain do not occur in the elderly who have gout arthritis / gout. The method of implementing this community service is in the form of providing education in the form of counseling assisted by giving leaflets to every community who visits Posyandu Dahlia, Bontomakio Village, Rappocini District, which is attended by 23 participants. The result obtained in this activity is that there is public awareness to improve behavior or eating patterns that have been applied so far. Participants who took part in this activity looked enthusiastic and motivated in living a healthy life to improve their health status.